2000
DOI: 10.1128/aem.66.7.3004-3009.2000
|View full text |Cite
|
Sign up to set email alerts
|

Geranic Acid Formation, an Initial Reaction of Anaerobic Monoterpene Metabolism in Denitrifying Alcaligenes defragrans

Abstract: Monoterpenes with an unsaturated hydrocarbon structure are mineralized anaerobically by the denitrifying ␤-proteobacterium Alcaligenes defragrans. Organic acids occurring in cells of A. defragrans and culture medium were characterized to identify potential products of the monoterpene activation reaction. Geranic acid (E,E-3,7-dimethyl-2,6-octadienoic acid) accumulated to 0.5 mM in cells grown on ␣-phellandrene under nitrate limitation. Cell suspensions of A. defragrans 65Phen synthesized geranic acid in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 32 publications
4
36
0
Order By: Relevance
“…For biomass production, the strain was cultivated on 30 mM limonene and 100 mM nitrate (24). A 1-liter preculture was inoculated in a 10-liter vessel of carbonate-buffered mineral salt medium at pH 7.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For biomass production, the strain was cultivated on 30 mM limonene and 100 mM nitrate (24). A 1-liter preculture was inoculated in a 10-liter vessel of carbonate-buffered mineral salt medium at pH 7.0.…”
Section: Methodsmentioning
confidence: 99%
“…Initial studies on potential metabolites of the degradation pathway identified isoterpinolene as metabolite that was apparently not further metabolized (23) and geranic acid as ionic intermediate present in nitrate-respiring cells that were grown on acyclic or cyclic monoterpenes, e.g. myrcene or limonene (24).…”
mentioning
confidence: 99%
“…In C. defragrans, the linalool dehydratase-isomerase catalyzes the hydration of the acyclic ␤-myrcene to (S)-(ϩ)-linalool as well as the isomerization to geraniol (7,35). The formation of geranic acid was observed in vivo and in vitro (24), indicating the presence of dehydrogenases catalyzing the oxidation of the allyl alcohol geraniol to geranic acid, most probably via geranial. So far, the only geraniol dehydrogenases (GeDHs) characterized on the molecular level come from sweet basil, Ocimum basilicum (25), and the astigmatid mite Carpoglyphus lactis (37).…”
mentioning
confidence: 98%
“…Some information exists on conversion of terpenes under anaerobic conditions (Harder & Probian, 1995;Hylemon & Harder, 1998). Acyclic terpenes such as geranylate have been described as metabolites of cyclic terpene-utilizing anaerobes (Heyen & Harder, 2000). Aerobically, citronellol can be used as a single source of carbon and energy only by Pseudomonas citronellolis (Seubert, 1960;Seubert & Fass, 1964a, b) and a few related species such as Pseudomonas aeruginosa, Pseudomonas mendocina (Cantwell et al, 1978) and Pseudomonas delhiensis (Prakash et al, 2007).…”
Section: Introductionmentioning
confidence: 99%